COMPOSITION AND AMOUNT OF MARINE DEBRIS DISTRIBUTED TO MANGROVE ECOSYSTEMS IN KUPANG CITY, EAST NUSA TENGGARA, INDONESIA - lumban nauli lumban toruan; Selviana Mboro; Lady Cindy Soewarlan (Biology Department, Mathematics and natural science, Tadulako University, 2022)
The unique mangrove root system is a gathering place for small and large waste. The density of the population results in varied activities so that the waste produced in various types, quantities and sizes can be distributed to the mangrove area either through rivers or carried by the wind. The purpose of this study was to determine the type and amount of waste in the mangrove ecosystem in Kupang City. The method used is observation. Sampling was carried out by installing a transect perpendicular to the sea along 70 m at the place with the highest abundance of waste and the thickness of the mangrove reached 50-100 meters. There are 6 transects installed at the study site and each transect is divided into three zones consisting of three quadrants with a size of 30 x 10 m2. The distance between quadrants is 20 m with the first quadrant being at the first point where mangroves are found. The results of the study found that the composition of the types of waste scattered in the mangrove ecosystem of Kupang City were 88,91% plastik with a total of 15,628 pieces, cloth (4,21%) with a total of 640 pieces, other waste (3,97%) with a total of 604 pieces, cork/foam (1,18%) with a total of 148 pieces, rubber (0,57%) with a total of 86 pieces, metal (0,29%) with a total of 44 pieces, glass and ceramics (0,15%) with a total of 11 pieces, then paper and cardboard (0,05%) with a total of 7 pieces. Types of plastic waste, fabrics, others, rubber and metal have a greater amount in the first zone, cork / foam is the most in the second zone then paper and cardboard are most found in the first and third zones, while glass and ceramics are the most in zone three.